Pengaruh Penggunaan High Quality Feed Supplement terhadap Konsumsi dan Kecernaan Nutrien Sapi Perah Awal Laktasi (The Effect of High Quality Feed Supplement Addition on the Nutrient Consumption and Digestibility of Early Lactating Dairy Cow) - Andriyani Astuti; Ali Agus; Subur Priyono Sasmito Budi (Buletin Peternakan, 2009)
The research was intended to know the effect of high quality feed supplement (HQFS) in the ration of first lactation dairy cow on nutrient consumption and digestibility. Twelve dairy cows of Friesian Holstein crossbred fromthe Cooperative of Warga Mulya, Sleman. They were divided into three groups of treatment, namely control (K), substitution treatment (S), and supplementation treatment (A). Each treatment consisted of four cows. Group K fed concentrate only from Warga Mulya, while group S beside concentrate from Warga Mulya, amount of HQFS 300 gram/liter of milk produced was offered, and concentrate was reduced as much as the additional feed of HQFS. Group A was offered by concentrate Warga Mulya plus HQFS additionally for 300 gram/liter of milk per day. Water was provided ad libitum. The variable measured consisted of the feed consumption and digestion (dry matter (BK), crude protein (PK), total digestible nutrient (TDN), organic component (BO), crude fiber (SK), crude fat (LK), and nitrogen-free extract (BETN)). The variants of collected data were analyzed, using Completely Randomized Design one way classification. Results showed that there were significant difference (P<0.05) on BK, PK, TDN, BO, PK, SK, LK, and BETN consumption, while the digestion of BK, BO, SK, and LK did not indicate any differences. The digestion of PK and BETN were significantly different (P<0.05), i.e. A (66.09%), S (59.77%), and K (54.66%) on PK and A (75.30%), S(73.11%), and K (70.69%) on BETN. The conclusion was that the addition of HQFS of first lactation dairy cow would increase nutrient consumption and crude protein and nitrogen-free extract digestibility.(Key words: High quality feed supplement, Dairy cow, Consumption, Digestibility)